A Doctor Patient Portal for Effective Healthcare - Shmasuddin Mohammed Taiser; Md. Tarequl Islam; Muhammad Kamrul Hossain; Md. Sabir Hossain (Soegijapranata Catholic University, 2019)
This paper presents a noble approach to develop a digital healthcare system for Bangladesh, a country which is soon going to become a developing country. We made an online application to help the masses to get access to healthcare easily and effectively. The application consists of two modules, doctor/hospital information system and emergency services. It has user-friendly features for doctor appointment making. Also, it has a blood donor search option, ambulance calling option, patient’s report view option, doctors ranking options etc. The doctors ranking is a special feature which was calculated based on doctor’s educational qualification, experience, average count of appointments made by patients and patient’s feedback. Feedback form real users showed that this information system was very helpful for them. If implemented countrywide, this system of digital healthcare may pave the way for an effective healthcare service in Bangladesh.